2013
DOI: 10.1016/j.cyto.2012.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction marker levels are influenced by prothrombin and tumor necrosis factor-α gene polymorphisms in young patients

Abstract: a b s t r a c tPolymorphisms of genes encoding key factors for the control and activation of inflammatory response and coagulation cascade regulation may play a role in genetic susceptibility to acute myocardial infarction (AMI). This study sought to analyze the effect of TNF À308G/A and pro-thrombin (FII) 20210G/A polymorphisms on the laboratory parameters of young patients affected by AMI. Results indicated that TNF À308A positive genotype frequencies were increased in these patients and that a genetically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Substantive studies over the past decade have been making efforts to unmask the correlation between the G20210A SNP and MI. However, previous conflicting reports failed to draw a consistent conclusion, thereby making the association between the G20210A SNP and MI elusive 8 , 10 , 18 , 19 , 25 27 , 37 39 . The variance may result from different study designs and distinct ethnic backgrounds of subjects.…”
Section: Discussionmentioning
confidence: 96%
“…Substantive studies over the past decade have been making efforts to unmask the correlation between the G20210A SNP and MI. However, previous conflicting reports failed to draw a consistent conclusion, thereby making the association between the G20210A SNP and MI elusive 8 , 10 , 18 , 19 , 25 27 , 37 39 . The variance may result from different study designs and distinct ethnic backgrounds of subjects.…”
Section: Discussionmentioning
confidence: 96%
“…Of the 147 initially identified studies, 12 publications with 13 case-control studies were included in our analysis (Herrmann et al, 1998;Padovani et al, 2000;Koch et al, 2001;Tobin et al, 2004;Bennet et al, 2006;Hou et al, 2009;Ghaderian et al, 2011;Zeybek et al, 2011;Chu et al, 2012;Szabó, 2013;Vaccarino et al, 2013;Biswas et al, 2014). Figure 1 shows a detailed flowchart of the selection process.…”
Section: Study Identificationmentioning
confidence: 99%
“…Of those studies, one was a multiple-center study, and consisted of two case-control studies (Herrmann et al, 1998), while all others were single-center studies. Three studies investigated acute myocardial infarction (AMI) patients only (Ghaderian et al, 2011;Vaccarino et al, 2013;Biswas et al, 2014), while the other 10 case-control studies included mixed patients at varying stages of the disease (old, recent, or acute). All studies reported the genotype frequencies of cases and controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although great improvements have been achieved in the diagnosis and treatment of AMI, the short-and long-term mortality rates in AMI patients still remain high [3,4]. In addition, the onset age of AMI is becoming increasingly low [5,6]. Therefore, it is of great significance to investigate the pathogenesis of AMI in patients younger than 60 years.…”
Section: Introductionmentioning
confidence: 99%